1) -1,6
2) 1,4; 0,2
Пошаговое объяснение:
1) -0,77* 4/9 - 4/9 *2,83 = -4/9*(0,77+2,83) = -4/9 * 3,6 =
= - 3,6 : 9*4 = -0,4*4 = - 1,6
2) (5y-7)(2y-0,4) =0
(*вероятно, что здесь пропущена скобка перед двойкой)
5y-7=0 или 2y-0,4=0
5y=7 2y=0,4
y= 7:5 y = 0,4 :2
y = 1,4 y=0,2
1) -1,6
2) 1,4; 0,2
Пошаговое объяснение:
1) -0,77* 4/9 - 4/9 *2,83 = -4/9*(0,77+2,83) = -4/9 * 3,6 =
= - 3,6 : 9*4 = -0,4*4 = - 1,6
2) (5y-7)(2y-0,4) =0
(*вероятно, что здесь пропущена скобка перед двойкой)
5y-7=0 или 2y-0,4=0
5y=7 2y=0,4
y= 7:5 y = 0,4 :2
y = 1,4 y=0,2